Engagement Enhancement Strategy Thru Entrepreneurship Strengthening Programs, Psychological Capital, And Work Motivation - Ibnu Tamam; Widodo Sunaryo; Nancy Yusnita (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
This study aims to analyze the influence of entrepreneurship and psychological capital on employe engagement, with work motivation as a mediating variable, among operational employes of PT Enseval Putera Megatrading Tbk Bogor and Depok branches. The research method uses a quantitative approach with a survey technique of 100 respondents, and data analysis is performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The research findings indicate that entrepreneurship and psychological capital have a positive and significant impact on work motivation, but neither has a direct significant impact on employe engagement. Conversely, work motivation was found to have a positive and significant impact on employe engagement and to act as a mediator between entrepreneurship and psychological capital and employe engagement. The coefficient of determination (R²) value of 0.530 indicates that the model's ability to explain employe work engagement is in the moderate category. This finding indicates that increased employe engagement can be achieved by strengthening work motivation driven by employes' entrepreneurial behavior and psychological capital. This research provides practical implications for management in developing work engagement improvement programs based on motivation and psychological capacity in the Indonesian healthcare distribution industry environment